2020
DOI: 10.17691/stm2020.12.2.11
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Lipid Profile and Glycated Hemoglobin as a New Prognostic Criterion for Type 2 Diabetes Mellitus Development and Progression

Abstract: The aim of the study was to assess correlations between the lipid profile and glycated hemoglobin in order to define their prognostic value as a criterion for the development and progression of type 2 diabetes mellitus (DM2) in individuals with metabolic syndrome and low body mass. Materials and Methods. The study included the results of examining 50 patients with metabolic syndrome (group 1), 50 with low body mass index (BMI) (group 2), 50 with DM2 (group 3), and 50 apparently healthy people (control group). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…This finding confirms earlier results by others. 10 , 39 , 44 In addition, it has been estimated that a decline in the HbA1c level by 0.2% could lower the mortality rate by 10%. 45 But other studies disputed the significant difference between the serum concentrations of cholesterol and triglycerides with relation to HbA1c level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding confirms earlier results by others. 10 , 39 , 44 In addition, it has been estimated that a decline in the HbA1c level by 0.2% could lower the mortality rate by 10%. 45 But other studies disputed the significant difference between the serum concentrations of cholesterol and triglycerides with relation to HbA1c level.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] The relationship between T2DM and dyslipidemia could be bidirectional. While the risk of coronary artery disease (CAD) is two to four-fold higher in subjects with T2DM, 9 several studies have shown a significant correlation between glycated Hemoglobin (HbA1c) and multiple lipid profile parameters in patients with T2DM s. [10][11][12] Thus, effective control of one could positively affect the other.…”
Section: Introductionmentioning
confidence: 99%
“…• Races: The disease is more common in some races and ethnic groups. • Age: Low HDL cholesterol and elevated triglycerides are associated with an increased risk of T2DM, especially in elderly [19]. • Polycystic ovary syndrome also increases diabetes risk.…”
Section: • Inactivitymentioning
confidence: 99%
“…Ischemic heart disease, a reduction in life expectancy, and stroke are all higher risks associated with diabetes [1,2]. Diabetic patients are significantly at increased risk for cardiovascular disease due to dyslipidemia, which is considered an irregular lipid profile, caused by insulin resistance [3]. As a result of the metabolic syndrome and insulin resistance, transporting free fatty acids to the liver through the portal circulation, enhancing lipolysis [4,5].…”
Section: Introductionmentioning
confidence: 99%